Insights from Primary Data Collection on Rice Food Loss in Vietnam - Kok, M.G.; Soethoudt, J.M.; Guo, X.; Axmann, H.B. (Wageningen University & Research, 2024)
In our work conducted from 2022 to 2024, we focused on establishing Food Loss (FL) country profiles (Axmann et al., 2024). Since Vietnam lacked primary data on FL, we generated the FL data through modelling approach. FL data were derived using a bottom-up, mass-flow model (Guo et al., 2020), which integrates production data, outputs, imports, and exports at the country level. Estimates of losses at various stages of the supply chain were adopted from Porter et al. (2016) to calculate FL across Vietnam’s production and trade systems. To assess FL-associated greenhouse gas (GHG) emissions, GHG emission factors from Porter et al. (2016) were applied to calculate emissions for each supply chain stage. Based on this study (Axmann et al., 2024), a key recommendation was to implement monitoring systems and/or collect primary data for hotspot food products and chain stages. This would help identify hotspots and develop FL reduction strategies with synergies for mitigating GHG emissions and optimizing nutrition, land-use, and water footprints.